Effect of General Specific and Combined Fitness Training on Muscular Endurance Performance Variables among Football Players: Effects of Different Fitness Training Programs on Muscular Endurance in Football Players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to “Effect of General Specific and Combined Fitness Training on muscular endurance performance among Football Players” for the purpose of the study sixty male football players were selected from in and around Guntur District of Andhra Pradesh and their age ranged from 18 to 21 years. The subjects chosen for the study were divided into four equal groups and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. general fitness training were given to group ‘A’ Specific fitness training were given to group ‘B’ combined fitness training were given to group ‘C’ and the control group ‘D’ were restricted to participate in any of the fitness training. The fitness training programmes were given for a period of twelve weeks. The obtained data’s were analysed by Analysis of Covariance and which was further subject of Scheffe’s Post hoc test, wherever the F-Ratio was found significant. The result of the study revealed that the General fitness, Specific fitness and combined fitness training programme were significantly increased muscular strength and endurance, among football players.